The Effects of Earnings Surprises in Quarterly Reports on S&P 500 Components - Rácz, Dávid Andor; Huszár, Gergely (Public Finance Quarterly, 2023)
In this article, we examine with event study methodology how quarterly corporate reports affect share prices. We examine two tightly connected questions: (1) are the effects of earnings surprises in the published earnings per share (EPS) immediately incorporated into the share prices, and (2) can differences in pricing reactions between the sectors of the general stock market and the tech companies, which are more uncertainly valued be shown? According to the results in case of positive and negative EPS surprises (deviation by more than ±2% from analyst consensus) price reactions are almost complete and happen in the same direction as the deviation promptly, which however are not followed by significant abnormal returns starting from the second day after the announcement. In the group of positive news, the price reaction stemming from EPS surprises proved to be significantly higher in case of tech companies, however there is no significant difference between the two groups in case of negative surprises.